Pengembangan Video Pembelajaran Berbasis Capcut Pada Materi Pernapasan Manusia - Donna Rhamdan (Justek : Jurnal Sains dan Teknologi, 2024)
Abstract:  The aim of this development is to produce learning video products CapCut based on viable and attractive human breathing material for student use. The model used in this development research is the Borg and Gall model. The stages consist of introduction, planning, development, expert validation, revision, field trials, final revision. Instrument data collection in the form of a questionnaire. The questionnaire used is a validation questionnaire experts to assess product suitability and student questionnaires to see attractiveness product.Validation results obtained from video learningbased CapCut in the developed human respiratory material is expressed in the form< a i=12> percentage good, as well as in average. The results of field trials were also carried out and the results were presentedand categorized attractiveness. So hopefully you can produce video learning based CapCuton human breathing materials declared feasible and interesting.Tfeasibility of the learning video can be seen from the results validator assessment. From validation material expert with a result of 82%, media expert with a result of 92%, language expert with results 80%, and expert practitioners with results 86.7%, so it can be interpreted that video learning is declared very feasible, then from students through groups small group taken from 6 students with results of 89.3% and from the large group which is taken from all students with a result of 92.7% so it can be means that the learning video is very interesting.Abstrak: Tujuan pengembangan ini adalah menghasilkan produk video pembelajaran berbasis CapCut pada materi pernapasan manusia yang layak dan menarik untuk digunakan siswa. Model yang digunakan dalam penelitian pengembangan ini adalah model Borg and Gall. Tahapannya terdiri dari pendahuluan, perencanaan, pengembangan, validasi ahli, revisi, uji coba lapangan, revisi akhir. Instrumen pengumpulan data berupa angket. Angket yang di gunakan yaitu angket validasi ahli untuk penilaian kelayakan produk dan angket siswa untuk melihat kemenarikan produk. Hasil validasi yang diperoleh dari video pembelajaran berbasis CapCut pada materi pernapasan manusia yang dikembangkan dinyatakan dalam bentuk presentase baik, serta di rata-rata. Hasil uji coba lapangan juga dilakukan dan hasilnya dipresentasekan dan dikategorikan kemenarikan. Sehingga diharapkan dapat menghasilkan video pembelajaran berbasis CapCut pada materi pernapasan manusia yang dinyatakan layak dan menarik. Kelayakan dari video pembelajaran dapat dilihat dari hasil penilaian validator. Dari validasi ahli materi dengan hasil 82%, ahli media dengan hasil 92%, ahli bahasa dengan hasil 80%, dan ahli praktisi dengan hasil 86,7%, sehingga dapat diartikan bahwa video pembelajaran dinyatakan sangat layak, kemudian dari siswa melalui kelompok kecil yang diambil dari 6 siswa dengan hasil 89,3% dan dari kelompok besar yaitu diambil dari keseluruhan siswa dengan hasil 92,7% sehingga dapat diartikan bahwa video pembelajaran sangat menarik.